Development of a recombinant human IgG1 monoclonal antibody against the TRBV5-1 segment of the T cell receptor for the treatment of mature T cell neoplasms - Pitaro, Michele; Antonini, Giovanni; Arcovito, Alessandro; Buccisano, Francesco; De Lauro, Alfredo; Irno Consalvo, Maria; Gallo, Valentina; Giacon, Noah; Mangiatordi, Giuseppe Felice; Pacelli, Maddalena; Pitaro, Maria Teresa; Polticelli, Fabio; et al. (Frontiers in Immunology, 2024)
BackgroundMature T-cell neoplasms arise from the neoplastic transformation of a single T lymphocyte, and all cells in a neoplastic clone share the same V segment in the beta chain of the T-cell receptor (TCR). These segments may represent an innovative target for the development of targeted therapies.MethodsA specific V segment of the TCR beta chain (TRBV5-1) was analyzed using bioinformatic tools, identifying three potential antigenic peptides. One of these peptides, selected for synthesis, was used to screen a library of human single-chain variable fragments (scFv) through phage display. One fragment demonstrated high affinity and specificity for the antigen and was used to produce a human monoclonal antibody of the IgG1 class.ResultsSurface plasmon resonance (SPR) studies confirmed the high affinity of the monoclonal antibody for the antigen in the nanomolar range. Flow cytometry analysis on patients’ samples demonstrated that the antibody, conjugated with a fluorochrome, selectively binds to tumor T lymphocytes expressing TRBV5-1, without binding to other lymphocytes or blood cell components.ConclusionsThe development of fully human IgG1 monoclonal antibodies targeting specific V segments of the TCR beta chain represents a potential therapeutic option for patients with mature T-cell neoplasms.